Treatment Outcomes of Sofosbuvir in Combination with Peg-Interferon and Ribavirin in the Treatment of Chronic HCV Genotype 3 (Evidence from Real Clinical Practice) - Borntrakulpipat, Chalermbhol (Srinagarind Medical Journal, 2024)
Background and Objective: Sofosbuvir is a nucleotide based NS5B polymerase inhibitor that exhibits PAN genotypic antiviral activity and has a high genetic barrier. This drug has been included in reimbursed universal health coverage in Thailand since 2018. The aim of this study was to report the results of this regimen in real life in Kalasin province, which has the third highest prevalence of HCV in Northeastern Thailand Methods: In this retrospective descriptive study, patients with chronic HCV genotype 3 were recruited to receive triple therapy with sofosbuvir 400 mg once a day, plus Peg-interferon (either Pegasys® or Peg-Intron®) administered through subcutaneous injection weekly, and weight-based ribavirin (600-1,000 mg) daily, divided into 2 doses, one after breakfast and one in the evening. All patients were enrolled between April 2019 and February 2021, and were eligible for inclusion if they were aged 18–70 years, had an HCV RNA level of 5,000 IU/mL or greater, and had a liver stiffness measurement of ≥ 7.0 kPa as assessed by Fibroscan®. The primary outcome was sustained virologic response at 12 weeks after discontinuation of antiviral drugs (SVR12). Secondary outcomes included safety, tolerance, and changes in laboratory values such as LFT, CBC, and creatinine. Results: The study initially enrolled 103 patients. However, one patient did not comply with the protocol, resulting in a total of 102 patients available for analysis. The mean age was 52 ± 8 years old. The oldest patient was 70 years old, and the youngest was 22 years old. The SVR12 for SOF/PEG-IFN/RBV was 100 %. However, one patient died due to an event unrelated to treatment, and another discontinued early due to chest discomfort that was not associated with the regimen. Resulting in an SVR12 rate of 100 out of 102 patients (98%) per intention to treat. No serious adverse events were reported in this study. Conclusion: The combination of Sofosbuvir, Peg-interferon, and even a low dose of Ribavirin (600 mg) for 12 weeks was highly efficacious, achieving an SVR12 rate of nearly 100% in Thai patients infected with genotype 3 HCV. This regimen was well-tolerated with excellent safety profiles.